Multiple Methods Research Investigating the Effectiveness of Arts/Mindfulness-Based Group Methods for the Development of Resilience in Children with High Needs - Coholic, Diana; Eys, Mark (Développement Humain, Handicap et Changement Social / Human Development, Disability, and Social Change)

(untitled) (Réseau International sur le Processus de Production du Handicap, 2011)
Our research explores the effectiveness of a holistic arts-based group program for the development of resilience in children with mental health problems. Art materials and experiential activities are used to teach children new skills and abilities, and to help them resolve issues that are interfering with healthy development. Mindfulness-based practices are an integral part of the group. Twenty-one children (8- 12 years of age) were assigned to one of three groups: (a) the holistic arts-based group, (b) an arts and crafts group (i.e., attention control) or (c) a wait-list control group. These groups nominally represent participants’ activities during the first 12-week period. However, each group eventually was exposed to the holistic arts-based group program over a subsequent 24-week period. Individual perceptions of resilience and self-concept were assessed at four time periods using The Resiliency Scales for Children and Adolescents (Prince-Embury) and the Piers-Harris Self-Concept Scale. A preliminary analysis (mixed design MANOVA) indicated a general interaction effect between the experimental groups and time, Wilks’ λ = .57, F (12,111.41) = 2.19, p < .05, η2 = .17. Follow up univariate analyses and interpretation of interaction effects demonstrated that the holistic arts-based group program significantly helped reduce the amount of self-reported emotional reactivity. This preliminary result (in the first year of a three-year research study) is consistent with previous qualitative analyses that found that the group program was suitable and feasible for children with high needs.